Windows of Insight: A Review on Stained Glass Research Trends - Leong, Kelvin; Sung, Anna (Talenta Publisher, 2024)
This study uses Scopus data from 1855 to 2023 to examine key trends and developments in stained glass research, showing a notable increase in academic work after 2000. This growth is linked to advances in digital technology and wider global access, allowing for interdisciplinary research combining materials science, engineering, and cultural studies. New technologies, such as hyperspectral imaging and laser cleaning, have significantly improved conservation methods. The study also shows an increasing contribution from the United States, alongside the continued leadership of Europe, with more diverse sources of funding reflecting global investment in stained glass research. By offering a comprehensive, long-term analysis, this review fills gaps in previous studies by addressing the lack of integrated research across different fields and regions. It provides useful insights for future research, policy-making, and conservation efforts, highlighting the global importance of stained glass. The findings emphasize its continuing relevance to art, technology, and cultural heritage preservation.